Pengembangan Keterampilan Kewirausahaan Siswa Sekolah Dasar Melalui Program Market Day - Dewi, Kania; Ramdan Samadi, Mochammad; Hermansyah, Yus; Nurishlah, Laesti (Prodi PGMI STAI Sabili Bandung, 2023)
This study explores the development of entrepreneurial skills in elementary school students through the Market Day program. Using a qualitative approach with a literature study method, this research analyzes various sources to evaluate the impact and effectiveness of the program. Market Day provides a platform for students to directly experience entrepreneurial activities, including planning, production, marketing, and sales. The findings show that Market Day significantly enhances students' understanding of business concepts and fosters their interest in entrepreneurship. Additionally, with the support of teachers and parents, students gain meaningful and relevant learning experiences, preparing them to face real-world challenges. This study emphasizes the importance of integrating practical programs like Market Day into the curriculum to develop entrepreneurial skills from an early age, helping students become more independent and innovative individuals in the future.